Gender, childhood and early childhood education in the graduate programs in education (1996 to 2015) - Santos, Sandro Vinicius Sales dos (2020)
In this paper, it was proposed a review of Doctoral dissertations and Master’s theses defended between 1996 and 2015 in the Graduate Programs in Education in Brazil and that considered children as interlocutors in research on gender relations. The aim was to analyze the Brazilian academic production in the field of Education in order to understand the specificities of the investigations on gender, childhood and Early Childhood Education, based on the reading of dissertations and theses defended in the period mentioned. The analysis corpus comprised five Doctoral dissertations and 24 Master’s theses grouped into the following categories: gender pedagogies produced by adults for children; gender relations among children; and lack of adult skills regarding the gender relations experienced by children. The analysis highlighted the main theoretical and methodological currents present in the investigation on the theme, emphasized the similarities and differences in academic production and stressed the recent constitution of a research field in Brazilian Graduate Programs.